Phytochemical Screening Of Abutilon Muticum (Del.Ex Dc.) And Celosia Argentea Linn - GAUTAM GIRENDRA KUMAR; VIDHYASAGAR GALI (International Journal of Pharma and Bio Sciences, 2011)
Medicinal plants have been used in all cultures throughout history. Extensive scientific documentation now exists concerning their use for health conditions including many disorders. Medicinal plants are of great importance to the health of individuals and communities. Hence the Author proposes to screen the some above mentioned drugs. The present paper deals with the screening of various phytochemical present in various extract viz., Methanol (80%), Distilled water with chloroform (2.5%) of Abutilon muticum (Del.ex DC.) and Celosia argentea Linn.